Sensory seeking and its influence on sustained attention performance in adult males with Autism Spectrum Condition - Takashi Itahashi; Ryuta Aoki; Motoaki Nakamura; Haruhisa Ohta; Ryu-ichiro Hashimoto (Scientific Reports)
Abstract Atypical sensory responses and seeking behaviors constitute the core symptoms of autism spectrum condition (ASC). There are possible links between atypical sensory profiles and attentional challenges in ASC. Due to the paucity of studies in adults, the nature of attentional challenges and their associations with sensory profiles in autistic adults remain elusive. Here, we investigated sustained attention performance and its associations with sensory profiles in 28 autistic adult males and 23 typically developing controls (TDCs). A gradual-onset continuous performance task and the Adolescent/Adult Sensory Profile were employed to assess sustained attention performance and sensory profiles, respectively. Our results revealed that the two groups exhibited comparable sustained attention performance quantified by d-prime. A statistically significant negative correlation between d-prime and sensory seeking was observed only in the ASC group. Moreover, an interaction effect of group-by-sensory seeking was observed in d-prime, suggesting a unique interplay between sensory profiles and attention in autistic individuals. In the ASC group, omission error rate and post-error slowing were statistically significantly associated with difficulties in social communication and interactions. These results contribute to understanding attentional processes in ASC and highlight the potential influence of sensory profiles on cognitive functions in this population.